KEBERHASILAN REHABILITASI TERUMBU KARANG AKIBAT PERISTIWA BLEACHING TAHUN 2016 DENGAN TEKNIK TRANSPLANTASI - Rani, Chair; Tahir, Akbar; Jompa, Jamaluddin; Faisal, Ahmad; Yusuf, Syafyudin; Werorilangi, Shinta; Arniati, Arniati (Jurnal Ilmu Kelautan SPERMONDE, 2017)
The purpose of this study was to analyze the succesfullnes use of two coral reef transplantation methods in the rehabilitation ofcoral reefs damaged by the phenomenon of bleaching in 2016 at the waters of Liukangloe Island, Bulukumba, South Sulawesi.In this study two methods were implemented, i.e. methods frame-spider and methods of nails-natural substrates, with 5 unitsas replication, respectively. A total of three kinds of branching corals weretransplanted, namely Acropora robusta, Poritescylindrica, and Pocillopora verrucosa. On each unit transplantation models, attached 6 coral fragments with branch length of5-12 cm for each kind of corals. A total of 3 fragments for each species of corals were labeled and coded for the survival rateand absolute growth monitoring. All five unit of experiments on each model are placed on two areas separately and placedrandomly with depths ranging from 3-4 m in the northern part of island. Observations survival rate and absolute growth of coraltransplant were conducted for every 2 weeks for 28 days by counting the dead coral fragment or missing and measure the lengthof transplant coral branch with a measuring ruler. The effectiveness of the two methods was analyzed based on the survival andgrowth of the absolute value of coral transplant. Survival rate were analyzed descriptively and the average values of absolutegrowth were analyzed by t-student. The use of frame-spider methods and methods of nails-natural substrates as effective inrehabilitating the coral reefs from bleaching phenomenon based on the parameters of survival and growth of Acropora robusta,Porites cylindrica, and Pocillopora verrucosaKeywords: Transplantation methods, coral reef, bleaching coral, Liukang Loe Island